The Effectiveness of English Learning Speech Assistant (ELSA) Speak Application to Improve Speaking Skill at the Tenth Grade of Senior High School - Melvi Faliska Arfandi; Wisran; Yuyun Ruqiyyat Said (Universitas Islam Negeri Palopo, 2026)
This study aimed to investigate the effectiveness of the English Learning Speech Assistant (ELSA) Speak application in improving students’ speaking skills at the tenth grade of SMAN 2 Palopo. This research employed a pre-experimental design using one-group pre-test and post-test design. The sample consisted of 32 students selected through purposive sampling. The instrument used in this research was a speaking test focusing on three aspects: pronunciation, vocabulary, and fluency. The data were analyzed using descriptive statistics, including mean score and standard deviation, and inferential statistics using a paired sample t-test through SPSS version 24. The findings revealed that students’ speaking skills improved after the implementation of the ELSA Speak application. The mean score increased from 59.59 in the pre-test to 68.69 in the post-test. Furthermore, the result of the t-test showed that the significance value was lower than 0.05, indicating that there was a significant difference between the pre-test and post-test results. This indicates that the use of the ELSA Speak application was effective in improving students’ speaking skills, particularly in pronunciation, vocabulary, and fluency. Therefore, it can be concluded that the ELSA Speak application is an effective learning medium to enhance students’ speaking performance.